Effect of Age and Sex on Human Drug Metabolism. Issue 5775 (11th September 1971) - O'Malley, K.; Crooks, J.; Duke, Eileen; Stevenson, I. H.
Abstract : The capacity of inpatients in a geriatric hospital to metabolize drugs was measured. The mean plasma half-life values with antipyrine and with phenylbutazone were found to be 45% and 29% greater respectively in patients than in young controls. When women alone were considered the half-life of antipyrine was 78% longer in the elderly group. In a number of elderly individuals the rate of metabolism of these two drugs was found to be extremely slow. This decreased ability to metabolize drugs may contribute to the known high incidence of adverse drug reactions in the elderly. Within the control group a significant sex difference in the rate of antipyrine metabolism was found, the mean half-life being 30% longer in the males. It is clear from these results that the age and sex of subjects must be taken into account in studies of human drug metabolism.